A conduta médica e a caracterização do erro - Graziela Gobbato (Scientia Iuris, 2002)
This article discerns a theoretic idea about the medical conduct and the mistake features on this profession, so that the recognition of the mistake itself happens though submitting the service acts to the patient; where disciplinary competent specialists perform. The medical mistake is faced by juridical means, through the gathering of proof; refining of the factors that caused the eventual mistake, damage or injury to the patient. Theoretically, techniques, methods, conscience and scientific knowledge used to achieve the success of the performance exempt the professional from eventual medical mistakes; however, with the occurrence and evidence of unskilfulness, imprudence and negligence the probability of confirming the mistake is able to make the professional civilly responsible for the patient's unexpected results, what might imply in re-execution or indemnity. Este artigo vislumbra uma apreciação teórica sobre a conduta médica e a caracterização do erro no exercício da profissão de medicina, modo pelo qual, o reconhecimento do erro propriamente dito, dá-se através da submissão aos atos de prestação de serviços ao paciente, onde especialistas com competência disciplinar atuam. O confronte do erro médico ocorre juridicamente, através da junção de provas, do refinamento dos fatores que causaram o eventual erro, dano ou lesão ao paciente. Teoricamente, técnicas, métodos, consciência e conhecimento científico utilizados para o sucesso do trabalho, isentam o profissional de eventuais erros médicos, porém, na ocorrência e comprovação de imperícia, imprudência e negligência, a probabilidade de confirmação do erro torna-se capaz de responsabilizar o profissional civilmente por resultados não esperados pelo paciente atendido, o que poderá transformar-se em reexecução ou indenização.